Role of AMF on plant growth, nutrient uptake, arsenic toxicity and chlorophyll content of chili grown in arsenic amended soil (Bangladesh Journal of Agricultural Research, 2013)
Mycorrhizal fungi have their most significant effect on plant growth and have shown to reduce arsenic contamination to chili. The present experiment was carried out to determine the influence of AMF inoculation on plant growth, nutrient uptake, arsenic toxicity, and chlorophyll content of chili grown in arsenic amended soil. Chili was grown in arsenic amended soils with or without mycorrhizal inoculation. Three levels of arsenic concentrations (10 ppm, 100 ppm, and 500 ppm) were used. The seed germination was affected more by the two treatment variables. Root length, shoot height, root fresh weight, shoot fresh weight, root dry weight, shoot dry weight were higher in AMF inoculated plants in comparison to their respective treatments and decreased significantly with the increase rate of arsenic concentrations. Less arsenic content, higher chlorophyll, and nutrient uptake were recorded in mycorrhiza inoculated chili plants. The present findings indicated that AMP inoculation not only minimize arsenic toxicity, but also can increase growth and nutrient uptake of chili. DOI: http://dx.doi.org/10.3329/bjar.v37i4.14388 Bangladesh J. Agril. Res. 37(4): 635-644, December 2012